The role of biotechnology in a sustainable food supply - Popp, Jennie, 1966- (Cambridge University Press, 2012)
"This publication addresses the role of biotechnology in a sustainable food supply in the 21st century. What sets this book apart is the thread that connects the broad subject matters and diverse author group. The chapters focus on the challenges, opportunities, success stories, barriers and risks associated with biotechnology. Authors are experts from around the world with broad backgrounds, experiences, and points of view. They include experts in the international aid and development, leaders in the developments and use of biotechnology in food applications, experts in food safety and risk associated with the use of biotechnology, and leaders in cosidering social, political and ethical issues surrounding the use of technology. The greatest strength of this book is the experitise and professional respect held by our authors and their diversity"--Resumé vydavatele